A region‐specific modulation of sleep slow waves on interictal epilepsy markers in focal epilepsy. Issue 4 (6th February 2023) - Chen, Cong; Wang, Yunling; Ye, Lingqi; Xu, Jiahui; Ming, Wenjie; Liu, Xiaochen; Hu, Lingli; Ye, Hongyi; Xu, Cenglin; Wang, Yi; Wang, Zhongjing; Ding, Yao; et al.
Abstract: Objective: Sleep strongly activates interictal epileptic activity through an unclear mechanism. We investigated how scalp sleep slow waves (SSWs), whose positive and negative half‐waves reflect the fluctuation of neuronal excitability between the up and down states, respectively, modulate interictal epileptic events in focal epilepsy. Methods: Simultaneous polysomnography was performed in 45 patients with drug‐resistant focal epilepsy during intracranial electroencephalographic recording. Scalp SSWs and intracranial spikes and ripples (80–250 Hz) were detected; ripples were classified as type I (co‐occurring with spikes) or type II (occurring alone). The Hilbert transform was used to analyze the distributions of spikes and ripples in the phases of SSWs. Results: Thirty patients with discrete seizure‐onset zone (SOZ) and discernable sleep architecture were included. Intracranial spikes and ripples accumulated around the negative peaks of SSWs and increased with SSW amplitude. Phase analysis revealed that spikes and both ripple subtypes in SOZ were similarly facilitated by SSWs exclusively during down state. In exclusively irritative zones outside SOZ (EIZ), SSWs facilitated spikes and type I ripples across a wider range of phases and to a greater extent than those in SOZ. The type II and type I ripples in EIZ were modulated by SSWs in different patterns. Ripples in normal zones decreased specifically during the up‐to‐down transition and then increased after the negative peak of SSW, with a characteristically high post‐/pre‐negative peak ratio. Significance: SSWs modulate interictal events in an amplitude‐dependent and region‐specific pattern. Pathological ripples and spikes were facilitated predominantly during the cortical down state. Coupling analysis of SSWs could improve the discrimination of pathological and physiological ripples and facilitate seizure localization.